2010
DOI: 10.1051/forest/2009128
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la longueur de la portée des sondes de dissipation thermique de type Granier sur des mesures de densité de flux de sève

Abstract: Abstract• Granier-type thermal dissipation sensors measure sap flux density (u) by using the temperature difference between the heater and the reference probe. To detect u correctly, heat must not be transferred to the reference probe by thermal conduction. The distance across which heat can be transferred by conduction is important for the span length of a sensor and spacing of a number of sensors.• To validate span lengths and spacing of sensors, we used numerical simulations to calculate the potential dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, a trade-off exists between minimizing errors associated with heating the reference probe at night and errors caused by thermal gradients (Lu et al 2004). Iida and Tanaka (2010) reported no difference in F S estimates made during the growing season on Pinus densiflora trees when probes were spaced 4 or 15 cm apart, suggesting that substantial probe separation is not necessary. Our calibration compensated for any potential interaction that might have occurred between the heater and reference probes, suggesting another reason why species-specific calibrations are important for improving accuracy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a trade-off exists between minimizing errors associated with heating the reference probe at night and errors caused by thermal gradients (Lu et al 2004). Iida and Tanaka (2010) reported no difference in F S estimates made during the growing season on Pinus densiflora trees when probes were spaced 4 or 15 cm apart, suggesting that substantial probe separation is not necessary. Our calibration compensated for any potential interaction that might have occurred between the heater and reference probes, suggesting another reason why species-specific calibrations are important for improving accuracy.…”
Section: Discussionmentioning
confidence: 94%
“…This 4 cm spacing distance is similar to the 5 cm distance used by Granier (1985) to develop the original a and b parameter values for the thermal dissipation technique. In a study of the effect of spacing on the accuracy of thermal dissipation measurements, Iida and Tanaka (2010) found that sensor spacing (4 or 15 cm) did not impact mean daily F S during the growing season. If spacing between the heater and reference probe was to influence F S estimates, it would likely do so by influencing DT max as heat should move upward when transpiration is occurring and only influence the reference probe when transpiration is not occurring or is very low.…”
Section: Thermal Dissipation Sensor Construction and Usementioning
confidence: 99%
“…Externally, the probes are provided with a coil winding of an insulated resistance constantan wire (copper–nickel alloy). Although in many works this distance was changed [27,39], we decided to keep it at 10 cm to avoid underestimation of sap flow [40]. Before to insert the sensors in the stem, their windings are inserted in a metal sleeve shaped as an aluminum micro-tube, 2 mm in diameter [41] that makes the thermal exchange with the wood more uniform.…”
Section: Methodsmentioning
confidence: 99%
“…The power supply for the heater of each sensor was controlled by the regulator (GN‐P; Environmental Measurement Japan, Co., Ltd., Tokyo, Japan), and the outputs of the sensor were sampled every 10 s, with 10‐min averages recorded using data loggers (CR1000; Campbell Scientific). F D was then calculated using a procedure described in the literature (Iida et al , ; Iida and Tanaka, ), with a correction applied (Clearwater et al , ) in cases when SW was less than the sensor length (Table ). The main objective of measuring the sap flux density was to determine the seasonal changes in transpiration, the timing of leaf fall and flush, and the relative importance of transpiration during the dry season on an annual scale for each tree.…”
Section: Methodsmentioning
confidence: 99%